Retinal periphlebitis in ulcerative colitis. - Kelly, I; Frith, P; Hyman, N; Jewell, D (BMJ Publishing Group, 1990)
A man presented with unilateral visual blurring associated with bilateral retinal periphlebitis which was felt to be a complication of his biopsy-proven active ulcerative colitis. Retinal periphlebitis has been associated rarely with some forms of colitis but we can find no report of its occurrence in association with ulcerative colitis although other ocular inflammatory disorders are well recognized.